COVID-19 pandemic influence on perceived exposure to chemical substances in Latvia: data from a focus group discussion and the HBM4EU citizen survey - Akūlova, Lāsma; Paegle, Linda; Mārtiņsone, Inese; Vanadziņš, Ivars; Knudsen, Lisbeth E.; Matisāne, Linda (Frontiers in Public Health, 2024)
Introduction The COVID-19 pandemic has globally influenced the exposure of populations to chemical substances through various channels. This study aims to evaluate the tendencies of the use of chemical products in Latvia amidst the pandemic. Answers from 597 respondents (26.6% male, 73.4% female, mean age 46.0 ± 12.2) which were gathered as part of the HBM4EU (Human Biomonitoring Initiative) citizen survey and 8 focus group participants were used. Methods The study utilized data from the HBM4EU citizen survey and conducted focus group discussions to understand the impact of the COVID-19 pandemic on chemical product usage in Latvia. Survey responses were analyzed to identify changes in exposure to chemicals, particularly in relation to disinfection agents and household products. Results More than two-thirds of survey participants reported increased exposure to chemicals during the COVID-19 pandemic, mainly related to the use of disinfection agents and household products. About 2-in-5 (39.8%) of survey respondents considered that the COVID-19 pandemic has increased their interest in exposure to chemicals. The excessive use of disinfectant products is the main concern of citizens (mentioned by 66.7%, n = 389). Also, two focus group participants noted that the use of disinfectant products is too widespread and should be minimized. Discussion The findings suggest that the COVID-19 pandemic has not only increased the use of chemical products in Latvia but also promoted an interest in safe and healthy use of chemicals which could be useful to raise the awareness of the general public.